2004
DOI: 10.1017/s0030605304000304
|View full text |Cite
|
Sign up to set email alerts
|

Range contraction in the pampas meadowlark Sturnella defilippii in the southern pampas grasslands of Argentina

Abstract: The Vulnerable Pampas meadowlark Sturnella defilippii (Family Icteridae) is a Neotropical grassland bird that suffered a severe population reduction and range contraction during the 20th century. Formerly distributed across most of the pampas grasslands, it is now confined to the southern tip of its original range. There are small groups of wintering birds in southern Brazil, a small reproductive population in eastern Uruguay, and the main reproductive population occurs on the southern pampas grasslands of Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The regional extinction of Eskimo Curlew may be at least partly explained by habitat transformation and heavy hunting in its nesting and wintering areas (Chebez 2008). Additional causes of bird decline include illegal capture for pet trade (Saffroncowled Blackbird Xanthopsar flavus, Fraga et al 1998 andPampas Meadowlark Sturnella defilippi, Tubaro andGabelli 1999), hunting for feathers, leather and food for humans (Greater Rhea Rhea americana, Navarro and Martella 2008), poisoning by pesticides, as already mentioned in the case of Swainson's Hawk (Goldstein et al 1996), and increased brood parasitism by Shiny Cowbird Molothrus bonariensis, a species that has been favoured by habitat transformation brought about by agricultural development (Gabelli et al 2004).…”
Section: Birdsmentioning
confidence: 92%
See 1 more Smart Citation
“…The regional extinction of Eskimo Curlew may be at least partly explained by habitat transformation and heavy hunting in its nesting and wintering areas (Chebez 2008). Additional causes of bird decline include illegal capture for pet trade (Saffroncowled Blackbird Xanthopsar flavus, Fraga et al 1998 andPampas Meadowlark Sturnella defilippi, Tubaro andGabelli 1999), hunting for feathers, leather and food for humans (Greater Rhea Rhea americana, Navarro and Martella 2008), poisoning by pesticides, as already mentioned in the case of Swainson's Hawk (Goldstein et al 1996), and increased brood parasitism by Shiny Cowbird Molothrus bonariensis, a species that has been favoured by habitat transformation brought about by agricultural development (Gabelli et al 2004).…”
Section: Birdsmentioning
confidence: 92%
“…The most important factor behind these changes is thought to be the loss of adequate reproductive habitat (Cozzani and Zalba 2009), due to conversion of grasslands into agricultural fields and afforestation, as well as cattle grazing and drainage of wetlands (Fraga et al 1998;Fernández et al 2003;Di Giacomo and Di Giacomo 2004;Gabelli et al 2004). The regional extinction of Eskimo Curlew may be at least partly explained by habitat transformation and heavy hunting in its nesting and wintering areas (Chebez 2008).…”
Section: Birdsmentioning
confidence: 98%
“…The purpose of this research was to study the spatial ecology of Geoffroy's cat in a wet area of the Pampas in Buenos Aires province, Argentina. The intense transformation of natural grassland ecosystems has already caused the local extinction/reduction of many vertebrates (Chebez, 1994; Gabelli et al , 2004), and the effect on small cat populations is little understood. As the Pampas grassland ecoregion occupies a large proportion of O. geoffroyi' s distribution range (Oliveira, 1994; Lucherini, Soler & Luengos Vidal, 2004), understanding its use of space and habitats in the grassland ecosystems is crucial for the future design of conservation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have examined patterns of range contractions. Exceptions include investigations by Channell and Lomolino (2000b), Gabelli et al (2004), Laliberte and Ripple (2004), and Scott-Morales et al (2004). Initially, biogeographers suggested that the range contraction of a species was likely to occur toward the center of its geographic distribution (Shelford 1911, Kendeigh 1974, Hengeveld and Haeck 1982.…”
mentioning
confidence: 99%